2013
DOI: 10.1080/03004279.2013.822013
|View full text |Cite
|
Sign up to set email alerts
|

Child-led enquiry in primary science

Abstract: This research describes and evaluates the application of a child-led approach to scientific enquiry (the Community of Scientific Enquiry, CoSE) to children aged 8–11 (Key Stage 2) in Northern Ireland. Primary teachers were introduced to CoSE at a workshop and asked to evaluate its implementation with their class. Results from children (n = 364) and teachers (n = 19) found that CoSE engaged children with their science learning, and also developed confidence and oracy. However, teachers require more experience d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…All of them agreed that they introducing a philosophical discussion in your classroom: an example of a community of enquiry in a greek primary school enjoyed their participation in the P4C sessions. This is in line with the results from previously conducted research in Northern Ireland which investigated the perceptions of 364 students and 19 teachers who participated in a sub-category of P4C (DUNLOP; COMPTON; CLARKE; MCKELVEY-MARTIN, 2015). It is worth noting that the conducted interviews with 16 teenagers in Greece after P4C…”
Section: Do Students Enjoy P4c Sessions and What Improvements They MIsupporting
confidence: 77%
“…All of them agreed that they introducing a philosophical discussion in your classroom: an example of a community of enquiry in a greek primary school enjoyed their participation in the P4C sessions. This is in line with the results from previously conducted research in Northern Ireland which investigated the perceptions of 364 students and 19 teachers who participated in a sub-category of P4C (DUNLOP; COMPTON; CLARKE; MCKELVEY-MARTIN, 2015). It is worth noting that the conducted interviews with 16 teenagers in Greece after P4C…”
Section: Do Students Enjoy P4c Sessions and What Improvements They MIsupporting
confidence: 77%
“…Low performing students appeared to have benefited more from generating questions compared to their higher performing counterpart (Berry & Chew, 2015). Student-generated questions have been tried with Key Stage 2 students (Dunlop, Compton, Clarke, & McKelvey-Martin, 2015) in which after given a stimulus, students volunteered questions. The class then voted on the questions they would like to explore.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…In their process group, they recorded learning that concerns instrument usage, conducting a standard procedure, planning an investigation, processing data, using data and reporting. Dunlop, Compton, Clarke, and McKelvey (2015) found that primary school teachers consider EA as an excellent method for achieving teaching objectives. Teachers in an in-service project in Sweden stated that EA is an important part of science education, because it connects theory to practice and familiarizes students with scientific objects and phenomena.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Additionally, they stated that they liked doing something different, being responsible for their own learning and having the ability to manipulate things and communicate with their friends about it. Research was conducted by Dunlop et al (2015) with 8-11 years old students to evaluate a kind of inquiry (Community of Scientific Enquiry strategy) implemented in their classes. The students expressed favorable statements concerning the experimentation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%